Synthesis of coumarins derivatives via decarboxylative cross-coupling of coumarin-3-carboxylic acid with benzylic C(sp3)-H bond. Issue 46 (14th November 2018) - Hao, Shuang-hong; Li, Li-Xia; Dong, Dao-Qing; Wang, Zu-Li; Yu, Xian-Yong
Graphical abstract: Highlights: C(sp3)-H bond activation. Decarboxylative cross-coupling. Coumarins Derivatives synthesis. Abstract: The reaction of coumarin-3-carboxylic acid with benzylic C(sp3)-H bond was established in this paper. A series of 3-benzylcoumarin derivatives were efficiently isolated in moderated to high yield using Cu(OAc)2 as catalyst and TBPB as oxidant.